Relevant market in commercial aviation of the european union - Kociubiński, Jakub (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The purpose of this paper is to provide a brief overview of the issue of definition of relevant market in civil aviation within the European Union. The liberalization of the market since the early 1990s has led to a rapid increase in the number of airlines operating in the EU. The increase in the competitiveness of the market has brought many positive changes for passengers, such as lower fares and a better network of connections. At the same time it has created a risk that the airlines, in order to gain a competitive edge, would infringe the rules of competition. This is especially important in the context of the phenomenon that is the development of the airline alliances, which could lead to an abuse of a dominant position. A clear definition of the relevant market is a first step in an assessment of whether such an abuse occurred. This paper focus on the elements that Internal Market regulator, the European Commission, takes into consideration when defining relevant market in the airline industry.
Keywords: European Union; definition of relevant market in civil aviation; competition